Consecuencia lógica: modelos conjuntistas y aspectos modales - Barrio, Eduardo Alejandro (Revista de Filosofía, 2007)
According to Etchemendy, in attempting to offer an analysis of the modal features of the intuitive concept of logical consequence, Tarski has committed a modal fallacy. In this paper, I consider the thesis according to it is posible to analyze the modals properties of concept of logical consequence through of a generalization on set-theoretical interpretations. As is known, some philosophers have tried to argue for the transit from the general to the modal by showing that there are enough settheoretic interpretations so as to be able to represent the modal features of the intuitive concept of consequence. As is also known, those people have encountered a lot of difficulties. In the present paper, I will try to show that those problems are related not with the specific possibility of accounting for the modal features by means of a set-theoretic notion of model but with the possibility of coming up with a precise mathematical theory for the concept of interpretation, and, as such, they can be solved by way of appealing to the usual solutions to this problem.